Leptomonas pyrrhocoris: Genomic insight into Parasite's Physiology - Butenko, Anzhelika; Vieira, Tamara da Silva; Frolov, Alexander O; Opperdoes, Fred R; Soares, Rodrigo P; Kostygov, Alexei Yu; Lukeš, Julius; Yurchenko, Vyacheslav (Current genomics, 2018)
BACKGROUND: Leptomonas pyrrhocoris is a parasite of the firebug Pyrrhocoris apterus. This flagellate has been recently proposed as a model species for studying different aspects of the biology of monoxenous trypanosomatids, including host - parasite interactions. During its life cycle L. pyrrhocoris never tightly attaches to the epithelium of the insect gut. In contrast, its dixenous relatives (Leishmania spp.) establish a stable infection via attachment to the intestinal walls of their insect hosts. MATERIAL AND METHODS: This process is mediated by chemical modifications of the cell surface lipophosphoglycans. In our study we tested whether the inability of L. pyrrhocoris to attach to the firebug's midgut is associated with the absence of these glycoconjugates. We also analyzed evolution of the proteins involved in proper lipophosphoglycan assembly, cell attachment and establishment of a stable infection in L. pyrrhocoris, L. seymouri, and Leishmania spp. Our comparative analysis demonstrated differences in SCG/L/R repertoire between the two parasite subgenera, Leishmania and Viannia, which may be related to distinct life strategies in various Leishmania spp. The genome of L. pyrrhocoris encodes 6 SCG genes, all of which are quite divergent from their orthologs in the genus Leishmania. Using direct probing with an antibody recognizing the β-Gal side chains of lipophosphoglycans, we confirmed that these structures are not synthesized in L. pyrrhocoris. CONCLUSION: We conclude that either the SCG enzymes are not active in this species (similarly to SCG5/7 in L. major), or they possess a different biochemical activity.
Keywords: L. pyrrhocoris; Host-parasite interaction; Monoxenous trypanosomatids; Insect gut's attachment; SCG enzymes; LPG